Research on Structure and Characteristics of Gear System of Crossflow in Flow Domain of Reactor Core - CHEN Guangliang, ZHANG Hanqi, TAO Wenquan (Yuanzineng kexue jishu)
The spatial difference of the thermal-hydraulic state in reactor core is easy to lead to local high temperature, so the risk of material burning and fuel melting is introduced under the safe conditions of average temperature. The fine computational fluid dynamics analysis of reactor core can carefully identify the extreme values and distribution of sub-millimeter fluid velocity, pressure, temperature and other parameters in reactor core. However, in traditional research, the states of flow resistance, thermal resistance, flow mixing and other states are measured by the macroscopic integration of lines, surfaces and volumes, and the fine data of tens of millions or hundreds of millions of computing grids are mostly converted into hundreds or thousands of sets of average data, the physical state is reduced from three-dimensional to two-dimensional or one-dimensional state, and the spatial resolution is reduced from submillimeter to decimeter or lower, and the fine data cannot be effectively and fully utilized. Therefore, the fine flow characteristics of reactor core are studied. The distribution of secondary flow intensity, temperature, and temperature inhomogeneity coefficients in the axial direction in the domain of a 15×15 rod bundle fuel assembly was first analyzed, and the flow characteristics induced by the spacer grid with the mixing vane were found to be periodic on each span domain. After that, the spontaneous configuration characteristics of the fluid were explored, and the fine flow analysis method based on the mechanical gear system was designed and named as flow gear system. The structure of the flow gear system in the fluid domain and the characteristics of energy storage, drag reduction, the rate of decline in energy quality, spontaneous optimization, maintenance of large flow mixing and flow identification were investigated, and the order of the turbulence of reactor core was clarified. In addition, the transverse flow character with fixed-wall conditions in a small domain like 5×5 rod bundle analyzed with flow gear system clarifies the limitations, which was unable to identify the large flow gear and long transverse flow structures, so that some thermal-hydraulic physical information was lost. The results show that the transverse flow analysis strategy based on the flow gear system is valuable to guide the research of the transverse flow in fuel assembly, and the important roles in the transverse flow keeping the quality of kinetic energy have been clarified, which can be seen as a new and useful strategy and methodology for the fine thermal-hydraulic data in reactor core.